Graft copolymer, curable resin composition, and adhesive composition
The core-shell graft copolymer, with a rubber polymer core and a graft monomer shell, addresses the challenges of dispersing graft copolymers in epoxy resins by enhancing powder dispersibility and mechanical properties, such as impact resistance, while improving process costs and environmental impact.
Patent Information
- Application Number
- JP2023548959
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-08-18
- Filing Date
- 2022-08-18
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2042-08-18
AI Technical Summary
Existing methods for dispersing graft copolymers in epoxy resins face challenges such as high process costs, environmental concerns, and difficulties in achieving homogeneous distribution, particularly in the powder phase dispersion method due to high viscosity issues.
A core-shell graft copolymer with a rubber polymer core and a graft monomer shell, specifically designed to have a core content of 75-83% by weight and a shell thickness of 3-25% by weight, which enhances powder dispersibility in epoxy resins.
The graft copolymer achieves excellent powder dispersibility in epoxy resins, allowing for effective dispersion using the powder phase method, thereby improving process costs and environmental aspects while maintaining mechanical properties such as impact resistance.
Smart Images

Figure 0007660211000007 
Figure 0007660211000008 
Figure 0007660211000009
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0109742 filed on August 19, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference. The present invention relates to a graft copolymer which has excellent powder dispersibility in curable resins such as epoxy resins and can be used as a powder-phase impact modifier, a curable resin composition containing the same, and an adhesive composition containing the curable resin composition as a toughening agent. [Background technology]
[0002] Curable resins, such as epoxy resins, are used in various fields, such as electrical and electronic products, automobile parts, and building materials. The curable resins are used in combination with additives, such as inorganic fillers, release agents, and rubber particles having rubber-type properties, to complement physical properties and processability, rather than being used alone. Among these, epoxy resins often exhibit brittle properties, and therefore need to be improved in terms of impact resistance and adhesive strength.
[0003] In particular, when an epoxy resin is applied to an adhesive composition, if a toughening agent is applied to solve the above-mentioned problems of the epoxy resin, the impact resistance and adhesive strength can be improved by the toughening agent, but there is a possibility that the glass transition temperature, which is an inherent property of the epoxy resin, may change depending on the interaction between the epoxy resin and the toughening agent, which may cause a decrease in the performance of the adhesive composition or increase the viscosity of the adhesive composition, ultimately adversely affecting the workability.
[0004] Therefore, a method has been proposed in which a graft copolymer containing a rubber polymer is used in combination with an epoxy resin as an impact modifier, as a toughening agent that can improve impact resistance and adhesive strength without causing a decrease in the performance of the adhesive composition. The graft copolymer has a particle shape with a core-shell structure that includes a core containing a rubber polymer and a shell formed by graft polymerization on the core.
[0005] Here, in order to use the graft copolymer as an impact modifier for epoxy resin, the graft copolymer needs to be dispersed in the epoxy resin. Methods for dispersing the graft copolymer in the epoxy resin include a liquid phase dispersion method and a powder phase dispersion method.
[0006] In the liquid phase dispersion method, the graft copolymer is dispersed in an epoxy resin by a stepwise solvent replacement method in which the water is replaced with a solvent for the graft copolymer in a latex state in which the graft copolymer is dispersed in water, and the solvent is replaced again with an epoxy resin, as shown in Figure 1. This liquid phase dispersion method has the advantage that the graft copolymer is dispersed in a homogeneous distribution matrix of the epoxy resin, but has a storage problem in that the graft copolymer must be stored in a latex state until it is dispersed in order to be applied to the epoxy resin as an impact modifier, the process cost due to the solvent replacement is high, and there are environmental problems due to the graft copolymer and the water and solvent that are separated and discharged during the solvent replacement process.
[0007] The powder phase dispersion method has an advantage that the process cost is low because the dry powder aggregated from the graft copolymer latex, i.e., the powder phase graft copolymer, is directly dispersed in the epoxy resin as shown in FIG. 2. However, when the graft copolymer powder is directly introduced into the epoxy resin, the viscosity of the graft copolymer powder becomes very high, so that it is practically very difficult or impossible to disperse the graft copolymer powder.
[0008] Therefore, in order to apply a powder phase dispersion method to improve both process costs and environmental aspects when applying an impact modifier to a curable resin composition such as an epoxy resin, it is necessary to improve the powder dispersibility of the graft copolymer powder. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2006-104328 A Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been devised to solve the problems of the prior art, and an object of the present invention is to provide a graft copolymer which has excellent powder dispersibility in curable resins such as epoxy resins and can be used as a powder phase impact modifier, and a method for producing the same.
[0011] Another object of the present invention is to provide a curable resin composition in which the graft copolymer is applied to a powder phase, and a method for producing the same.
[0012] Another object of the present invention is to provide an adhesive composition using the above curable resin composition as a toughening agent. [Means for solving the problem]
[0013] In order to solve the above problems, the present invention provides a graft copolymer, a curable resin composition, and an adhesive composition containing the same.
[0014] (1) The present invention provides a core-shell graft copolymer comprising a core containing a rubber polymer; and a shell formed by graft polymerization of a graft monomer onto the rubber polymer, wherein the rubber polymer contains conjugated diene monomer units, the graft copolymer comprises a core of 75% by weight or more and 83% by weight or less, the core has an average particle size of 250 nm or more and 400 nm or less, and the shell has a thickness of 3 nm or more and 25 nm or less.
[0015] (2) The present invention provides a graft copolymer according to the above (1), wherein the graft monomer comprises an alkyl (meth)acrylate monomer.
[0016] (3) The present invention provides a graft copolymer according to the above (1) or (2), wherein the graft monomer comprises a methyl (meth)acrylate monomer, an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms, and a crosslinkable monomer.
[0017] (4) The present invention provides the graft copolymer according to the above (3), wherein the crosslinkable monomer is polyethylene glycol diacrylate or allyl methacrylate.
[0018] (5) The present invention provides a graft copolymer in any one of the above (1) to (4), wherein the graft monomer further contains an aromatic vinyl monomer.
[0019] (6) The present invention provides, in any one of (1) to (5) above, the graft copolymer comprising 79% by weight or more and 81% by weight or less of a core and 19% by weight or more and 21% by weight or less of a shell.
[0020] (7) The present invention provides the graft copolymer according to any one of the above (1) to (6), wherein the shell has a thickness of 5 nm or more and 22 nm or less.
[0021] (8) The present invention provides, in any one of the above (1) to (7), the graft copolymer having an average particle size of 250 nm or more and 500 nm or less.
[0022] (9) The present invention provides a curable resin composition comprising a continuous phase and a dispersed phase, the continuous phase comprising a curable resin, and the dispersed phase comprising the graft copolymer according to any one of (1) to (8) above.
[0023] (10) The present invention provides a curable resin composition according to (9) above, wherein the curable resin composition comprises 50% by weight or more and 99% by weight or less of a continuous phase and 1% by weight or more and 50% by weight or less of a dispersed phase.
[0024] (11) The present invention provides the curable resin composition according to (9) or (10), wherein the curable resin is an epoxy resin.
[0025] (12) The present invention provides a curable resin composition according to any one of the above items (9) to (11), wherein the curable resin composition has a viscosity at 25° C. of 1,500 Pa.s or less at 2.4 1 / s.
[0026] (13) The present invention provides an adhesive composition comprising a base resin, a toughening agent, and a urethane resin, the toughening agent being a curable resin composition according to any one of (9) to (12) above, and comprising 10% by weight or more and 20% by weight or less of the toughening agent.
[0027] (14) The present invention provides an adhesive composition according to (13), wherein the adhesive composition has a storage modulus (G') value of 900 MPa or more and 1,100 MPa or less at -35°C in a graph showing changes in storage modulus (G') as a function of temperature obtained by dynamic viscoelastic analysis of a cured specimen using an Advanced Rheometric Expansion System (ARES) (torsion mode, frequency of 1 Hz, strain of 0.1%, and heating rate of 5°C / min).
[0028] (15) The present invention provides an adhesive composition according to (13) or (14), wherein the adhesive composition has a storage modulus (G') value of 530 MPa or more and 630 MPa or less at 25°C in a graph showing changes in storage modulus (G') as a function of temperature obtained by dynamic viscoelastic analysis of a cured specimen using an Advanced Rheometric Expansion System (ARES) (torsion mode, frequency of 1 Hz, strain of 0.1%, and heating rate of 5°C / min).
[0029] (16) The present invention provides an adhesive composition according to any one of the above (13) to (15), wherein the adhesive composition has a viscosity at 25° C. at 2.4 1 / s of 250 Pa.s or more and 750 Pa.s or less. Effect of the Invention
[0030] The graft copolymer of the present invention has excellent powder dispersibility in curable resins such as epoxy resins, and has the effect of being dispersible in curable resin compositions by a powder phase dispersion method.
[0031] The curable resin composition of the present invention can apply a graft copolymer as an impact modifier to the powder phase, and has the effects of excellent productivity and excellent mechanical properties such as impact resistance due to the graft copolymer dispersed in the curable resin composition.
[0032] The adhesive composition of the present invention contains the curable resin composition as a toughening agent, and has the effect of being excellent in impact resistance and adhesive strength. [Brief description of the drawings]
[0033] [Figure 1] FIG. 1 is a process diagram showing an outline of a liquid phase dispersion method for dispersing a graft copolymer in an epoxy resin. [Diagram 2] FIG. 1 is a process diagram showing an outline of a powder phase dispersion method for dispersing a graft copolymer in an epoxy resin. [Diagram 3]1 is a transmission electron microscope image of a specimen prepared using the graft copolymer prepared in Example 3 of the present invention at a magnification of 10,000. [Figure 4] 1 is a transmission electron microscope image of a specimen prepared using an epoxy resin composition prepared using the graft copolymer of Example 3 of the present invention at a magnification of 25,000. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0034] In the following, the present invention will be described in more detail to facilitate understanding of the present invention. The terms and words used in the description of the present invention and the claims should not be interpreted limited to their ordinary and dictionary meanings, but should be interpreted in a way that is consistent with the technical ideas of the present invention, based on the principle that the inventor himself / herself can appropriately define the concepts of terms in order to best describe the invention.
[0035] In the present invention, the term "monomer unit" may refer to a component, structure, or substance derived from a monomer, and as a specific example, may refer to a repeating unit formed in a polymer by an input monomer participating in a polymerization reaction during polymerization of a polymer.
[0036] The term "composition" as used herein is inclusive of mixtures of materials which comprise the composition as well as reaction products and decomposition products formed from the materials of the composition.
[0037] The present invention provides a graft copolymer that can be used as an impact modifier in a curable resin composition. The graft copolymer according to the present invention has improved powder dispersibility in a curable resin such as an epoxy resin, and is a core-shell graft copolymer including a core containing a rubber polymer and a shell formed by graft polymerizing a graft monomer onto the rubber polymer, the rubber polymer includes a conjugated diene monomer unit, the graft copolymer includes 75% to 83% by weight of the core, the core may have an average particle size of 250 nm to 400 nm, and the shell may have a thickness of 3 nm to 25 nm, and thus has the effect of being able to be dispersed in a curable resin composition by a powder phase dispersion method.
[0038] According to one embodiment of the present invention, in the core-shell graft copolymer, the core may refer to the rubber polymer component itself that forms the core or core layer of the graft copolymer, and the shell may refer to a polymer component or copolymer component that is graft polymerized to the rubber polymer to form a shell or shell layer in the form of a shell that surrounds the core. That is, the core containing the rubber polymer may be the rubber polymer itself, and the shell may refer to a graft layer formed by graft polymerization of a graft monomer to the rubber polymer.
[0039] According to an embodiment of the present invention, the rubber polymer may include a conjugated diene monomer unit as a component for imparting impact resistance when the graft copolymer is applied as an impact modifier. As a specific example, the rubber polymer may be a conjugated diene rubber polymer. As a more specific example, the conjugated diene rubber polymer may be at least one selected from the group consisting of a homopolymer of a conjugated diene monomer and a copolymer of an aromatic vinyl monomer-conjugated diene monomer.
[0040] According to one embodiment of the present invention, the conjugated diene monomer of the rubber polymer may be at least one selected from the group consisting of 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, piperylene, 3-butyl-1,3-octadiene, isoprene, and 2-phenyl-1,3-butadiene, and a specific example thereof may be 1,3-butadiene.
[0041] According to one embodiment of the present invention, the aromatic vinyl monomer of the rubber polymer may be at least one selected from the group consisting of styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 1-vinylnaphthalene, 4-cyclohexylstyrene, 4-(p-methylphenyl)styrene, and 1-vinyl-5-hexylnaphthalene, and a specific example thereof may be styrene.
[0042] According to an embodiment of the present invention, the shell is a component for improving compatibility and mechanical properties when the graft copolymer is applied as an impact modifier, and may be a graft layer formed by graft polymerizing a graft monomer onto the rubber polymer as described above. As a specific example, the graft monomer graft polymerized onto the rubber polymer to form the shell may include an alkyl(meth)acrylate monomer.
[0043] According to one embodiment of the present invention, the alkyl (meth)acrylate monomer of the graft monomer may be an alkyl (meth)acrylate monomer having 1 to 12 carbon atoms, and specific examples thereof may be one or more selected from the group consisting of methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, and n-butyl acrylate.
[0044] According to one embodiment of the present invention, the alkyl (meth)acrylate monomer of the graft monomer may be two or more monomers selected from the group consisting of alkyl (meth)acrylate monomers having 1 to 12 carbon atoms, and specific examples thereof may be two or more monomers selected from the group consisting of methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, and n-butyl acrylate.
[0045] According to an embodiment of the present invention, the alkyl (meth)acrylate monomer of the graft monomer may be a methyl (meth)acrylate monomer; and an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms, in which case the weight average molecular weight of the shell can be lowered, and thus swelling of the shell can be minimized when the graft copolymer is dispersed in the curable resin, thereby preventing an increase in viscosity. In this case, the alkyl (meth)acrylate monomer may include 50 wt% to 99 wt%, 60 wt% to 90 wt%, or 70 wt% to 85 wt% of the methyl (meth)acrylate monomer; and 1 wt% to 50 wt%, 10 wt% to 40 wt%, or 15 wt% to 30 wt% of the alkyl (meth)acrylate monomer having 2 to 12 carbon atoms.
[0046] According to an embodiment of the present invention, the graft monomer may further include a crosslinkable monomer in addition to the alkyl (meth)acrylate monomer, that is, the graft monomer may include a methyl (meth)acrylate monomer, an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms, and a crosslinkable monomer.
[0047] According to an embodiment of the present invention, the crosslinkable monomer is used to improve the shell-forming ability by crosslinking during the formation of a shell by the graft monomer, and at the same time, to further improve the compatibility and mechanical properties of the shell. The crosslinkable monomer may be at least one selected from (meth)acrylic crosslinkable monomers such as ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, allyl (meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and vinyl crosslinkable monomers such as divinylbenzene, divinylnaphthalene, and diallyl phthalate. A specific example of the crosslinkable monomer may be polyethylene glycol diacrylate or allyl methacrylate.
[0048] According to an embodiment of the present invention, the graft monomer may further include an aromatic vinyl monomer, that is, the graft monomer may include a methyl (meth)acrylate monomer, an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms, and an aromatic vinyl monomer.
[0049] According to one embodiment of the present invention, the aromatic vinyl monomer of the graft monomer may be at least one selected from the group consisting of styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 1-vinylnaphthalene, 4-cyclohexylstyrene, 4-(p-methylphenyl)styrene, and 1-vinyl-5-hexylnaphthalene, and a specific example thereof may be styrene.
[0050] According to an embodiment of the present invention, when the graft monomer further includes an aromatic vinyl monomer, the aromatic vinyl monomer may be included in an amount of 0.1 wt % to 10.0 wt %, 0.5 wt % to 5.0 wt %, or 0.8 wt % to 2.0 wt % based on the total content of the graft monomer.
[0051] In order to enable the graft copolymer according to the present invention to be dispersed in a curable resin composition by a powder phase dispersion method, it is very important to control the core content and shell thickness in the graft copolymer.
[0052] According to an embodiment of the present invention, the graft copolymer may contain 75% by weight or more and 83% by weight or less of the core, and specifically, 75% by weight or more, 76% by weight or more, 77% by weight or more, 78% by weight or more, or 79% by weight or more, and 83% by weight or less, 82% by weight or less, or 81% by weight or less of the core. In addition, the graft copolymer may contain 17% by weight or more, 18% by weight or more, or 19% by weight or more of the shell, and 25% by weight or less, 24% by weight or less, 23% by weight or less, 22% by weight or less, or 21% by weight or less of the shell. When the graft copolymer is dispersed in the curable resin within the above content range of the core and shell, the compatibility between the curable resin and the graft copolymer is sufficiently ensured, and the swelling of the shell is minimized, thereby preventing an increase in viscosity. On the other hand, if the graft copolymer contains a core at a content lower than the above range, the shell content in the graft copolymer increases accordingly, and the shell, which has high affinity with the curable resin, swells, causing an increase in viscosity and a decrease in dispersibility. On the other hand, if the graft copolymer contains a core at a content higher than the above range, the compatibility of the curable resin and the graft copolymer decreases rapidly, and although the increase in viscosity due to the swelling of the shell can be prevented, there is a problem that dispersion is not substantially performed. On the other hand, the respective contents of the core and shell may be derived from the ratio of the contents of the rubber polymer and the graft monomer added during the preparation of the graft copolymer.
[0053] According to one embodiment of the present invention, the core may have an average particle size of 250 nm to 400 nm, and as a specific example, the average particle size may be 250 nm to 350 nm. Within this range, an increase in viscosity can be prevented when dispersing the graft copolymer in a curable resin.
[0054] According to one embodiment of the present invention, the thickness of the shell may be 3 nm or more, 4 nm or more, 5 nm or more, 6 nm or more, 7 nm or more, 8 nm or more, 9 nm or more, 10 nm or more, 11 nm or more, 12 nm or more, 13 nm or more, or 14 nm or more, and may be 25 nm or less, 24 nm or less, 23 nm or less, 22 nm or less, 21 nm or less, 20 nm or less, 19 nm or less, 18 nm or less, 17 nm or less, 16 nm or less, 15 nm or less, 14 nm or less, 13 nm or less, 12 nm or less, or 11 nm or less. Within this range, when the graft copolymer is dispersed in the curable resin, the compatibility between the curable resin and the graft copolymer is sufficiently ensured, while the swelling of the shell is minimized, thereby preventing an increase in viscosity. On the other hand, if the shell thickness is higher than the above range, there is a problem that the shell having high affinity with the curable resin swells, increasing the viscosity and decreasing the dispersibility, and if the shell thickness is lower than the above range, there is a problem that the graft copolymer exists in a particle form having low affinity with the curable resin, and thus the dispersibility is also decreased. The shell thickness can be adjusted by adjusting the content of the rubber polymer, or by adjusting the amount of the initiator and the activator added when the graft monomer is graft polymerized in the presence of the rubber polymer.
[0055] In this way, by adjusting the content of the core in the graft copolymer and the thickness of the shell according to the present invention, it becomes possible to disperse the graft copolymer in the curable resin composition by a powder phase dispersion method.
[0056] According to an embodiment of the present invention, the thickness of the shell can be calculated and confirmed by various methods. As a specific example, the thickness of the shell can be calculated from the average particle diameter of the core and the average particle diameter of the graft copolymer according to the following mathematical formula 1.
[0057] [Mathematical formula 1] Shell thickness (nm) = average particle size of graft copolymer (nm) - average particle size of core (nm)
[0058] In addition, the shell thickness can be confirmed by drying the graft copolymer in a vacuum oven to obtain a solid, preparing a thin section using a microtome, staining the section with osmium tetroxide vapor to prepare a specimen, photographing the specimen at 10,000 times magnification using a transmission electron microscope, and measuring the shell thickness of the graft copolymer particles.
[0059] In addition, the thickness of the shell can be confirmed by curing the epoxy resin composition prepared using the graft copolymer at room temperature using polyetheramine, preparing a thin section using a microtome, staining the section with osmium tetroxide vapor to prepare a specimen, photographing the specimen at 25,000 times magnification using a transmission electron microscope, and measuring the core particle size and shell thickness for each dispersed phase.
[0060] According to one embodiment of the present invention, the average particle size of the graft copolymer may be 250 nm or more, and may be 500 nm or less, 450 nm or less, or 400 nm or less. Within this range, an increase in viscosity can be prevented when the graft copolymer is dispersed in a curable resin.
[0061] The present invention also provides a method for preparing the graft copolymer, which includes the steps of: (S1) preparing a rubber polymer latex containing a conjugated diene rubber polymer; and (S2) preparing a graft copolymer latex containing a core-shell graft copolymer by adding a graft monomer in the presence of 75% by weight to 83% by weight (based on solid content) of the rubber polymer latex, and graft polymerizing the graft monomer, wherein the shell thickness of the graft copolymer prepared in the step (S2) may be 3 nm to 25 nm.
[0062] According to one embodiment of the present invention, in the method for preparing the graft copolymer, the type and content of the monomer for carrying out each step may be the same as the type and content of the monomer for the graft copolymer described above.
[0063] According to one embodiment of the present invention, the step (S1) is a step of preparing a conjugated diene rubbery polymer that forms a core or a core layer in a core-shell graft copolymer, and the step (S2) is a step of graft polymerizing the conjugated diene rubbery polymer to form a shell or a shell layer that surrounds the core, and is characterized in that the shell thickness is adjusted to 3 nm or more and 25 nm or less.
[0064] According to an embodiment of the present invention, each of the steps (S1) and (S2) may be carried out by emulsion polymerization, and may be carried out in the presence of an emulsifier and an initiator, as well as an electrolyte, a molecular weight regulator, an activator, etc. In carrying out the step (S1), the average particle size of the conjugated diene rubbery polymer particles may be controlled by the amount of emulsifier added, and in carrying out the step (S2), the thickness of the shell may be controlled by controlling the amount of rubbery polymer, the amount of initiator and / or activator added, or by continuously adding a graft monomer.
[0065] According to an embodiment of the present invention, the emulsifier may be at least one selected from the group consisting of fatty acid-based emulsifiers and rosin acid-based emulsifiers, and in this case, it has an excellent effect on latex stability.
[0066] According to an embodiment of the present invention, the amount of the emulsifier added in step (S1) may be 0.1 to 3.4 parts by weight, 1.0 to 3.3 parts by weight, 1.5 to 3.2 parts by weight, 2.0 to 3.2 parts by weight, or 2.1 to 3.1 parts by weight, based on 100 parts by weight of the monomer for polymerizing the rubber polymer.
[0067] According to one embodiment of the present invention, the amount of the emulsifier added in step (S2) may be 0.1 to 1.0 parts by weight, 0.1 to 0.5 parts by weight, or 0.1 to 0.3 parts by weight based on 100 parts by weight of the rubber polymer and monomer for polymerizing the graft copolymer. Within this range, excellent effect on latex stability is obtained.
[0068] According to an embodiment of the present invention, the step (S1) may be carried out using a water-soluble initiator that can be used in emulsion polymerization, and the water-soluble initiator may be potassium persulfate, sodium persulfate, ammonium persulfate, etc. The step (S2) may be carried out by radical polymerization using a peroxide-based, redox, or azo-based initiator that can be used in emulsion polymerization, and the redox initiator may be at least one selected from the group consisting of t-butyl hydroperoxide, diisopropylbenzene hydroperoxide, and cumene hydroperoxide, for example, and in this case, there is an effect of providing a stable polymerization environment. When the redox initiator is used, it may be carried out by further including ferrous sulfide, sodium ethylenediaminetetraacetate, and sodium formaldehyde sulfoxylate as a redox catalyst that is an activator, and the thickness of the shell may be adjusted to 3 nm or more and 25 nm or less by adjusting the input amount of the redox initiator and the redox catalyst. According to an embodiment of the present invention, the step (S2) may be carried out by continuously adding the graft monomer. When the step (S2) is carried out, if the graft monomer is added all at once before the start of the graft polymerization reaction, a problem of an increase in shell thickness may occur.
[0069] According to an embodiment of the present invention, the emulsion polymerization in steps (S1) and (S2) may be carried out in an aqueous solvent, and the aqueous solvent may be ion-exchanged water.
[0070] According to one embodiment of the present invention, the method for preparing the graft copolymer may include a step (S3) of coagulating and drying the graft copolymer latex prepared in the step (S2) to obtain a powder phase.
[0071] The present invention also provides a curable resin composition. The curable resin composition may contain the graft copolymer as an impact modifier, and as a specific example, the graft copolymer may be dispersed in a powder phase.
[0072] According to one embodiment of the present invention, the curable resin composition may include a continuous phase and a dispersed phase, the continuous phase may include a curable resin, and the dispersed phase may include the graft copolymer. As a specific example, the curable resin composition may include 50% by weight or more of the continuous phase, and may include 99% by weight or less, 80% by weight or less, or 70% by weight or less, and may include 1% by weight or more, 20% by weight or more, or 30% by weight or more, and may include 50% by weight or less of the dispersed phase.
[0073] According to one embodiment of the present invention, the curable resin may be a thermosetting resin or a photocurable resin, and a specific example thereof may be one or more selected from the group consisting of an epoxy resin, a phenolic resin, an unsaturated polyester resin, a melamine resin, and a urea resin, and a more specific example thereof may be an epoxy resin.
[0074] According to an embodiment of the present invention, the epoxy resin may include at least two epoxy bonds, and specific examples thereof may be one or more selected from the group consisting of bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD type epoxy resins, bisphenol E type epoxy resins, naphthalene type epoxy resins, biphenyl type epoxy resins, dicyclopentadiene type epoxy resins, phenol novolac type epoxy resins, aliphatic cyclic epoxy resins, and glycidylamine type epoxy resins.
[0075] According to one embodiment of the present invention, the curable resin composition may have a viscosity at 25°C at 2.4 1 / s of 1,500 Pa.s or less, and specific examples thereof include a viscosity of 1,450 Pa.s or less, 1,400 Pa.s or less, 1,350 Pa.s or less, 1,300 Pa.s or less, 1,290 Pa.s or less, 1,280 Pa.s or less, 1,270 Pa.s or less, 1,260 Pa.s or less, 1,250 Pa.s or less, 1,240 Pa.s or less, 1,230 Pa.s or less, or 1,220 Pa.s or less. and may be 100 Pa.s or more, 200 Pa.s or more, 300 Pa.s or more, 400 Pa.s or more, 500 Pa.s or more, 600 Pa.s or more, 700 Pa.s or more, 800 Pa.s or more, 900 Pa.s or more, 1,000 Pa.s or more, or 1,050 Pa.s or more, and within this range, when the curable resin composition is applied to the adhesive composition, there is an effect that the processability is improved while the impact resistance is excellent.
[0076] The present invention also provides a method for producing the curable resin composition.
[0077] According to one embodiment of the present invention, the method for preparing the curable resin composition includes: a step (S10) of preparing a graft copolymer latex including the graft copolymer; a step (S20) of preparing a graft copolymer powder by agglomerating and drying the graft copolymer latex prepared in the step (S10); and a step (S30) of preparing a curable resin composition by mixing a curable resin and the graft copolymer powder prepared in the step (S20), and the step (S30) may be performed by dispersing using a stirrer.
[0078] According to an embodiment of the present invention, the step (S10) for preparing the graft copolymer may be carried out by the above-mentioned method for preparing the graft copolymer.
[0079] According to one embodiment of the present invention, the step (S20) is a step for obtaining the graft copolymer prepared in the step (S10) as a powder phase, and may be performed by coagulating and drying the graft copolymer latex prepared in the step (S10).
[0080] According to one embodiment of the present invention, the aggregation in step (S20) may be performed by adding a coagulant to the graft copolymer latex. The aggregation in step (S20) may be performed by acid coagulation, such as with an aqueous sulfuric acid solution, and salt coagulation, such as with sodium chloride or sodium sulfate, and both the acid coagulation and the salt coagulation may be performed as necessary. In this case, the acid coagulation and the salt coagulation may be performed simultaneously or stepwise. When the aggregation is performed stepwise, the acid coagulation may be performed first and then the salt coagulation, or the salt coagulation may be performed first and then the acid coagulation. The aggregation in step (S20) may be performed in the presence of an organic dispersant as necessary.
[0081] According to one embodiment of the present invention, the drying in step (S20) may be carried out by a conventional drying method, and may further include a step of dehydrating the coagulated graft copolymer latex prior to drying, if necessary.
[0082] According to one embodiment of the present invention, the step (S30) is a step of mixing the curable resin and the graft copolymer by the powder phase dispersion method as described above when applying the graft copolymer as an impact modifier to the curable resin, and may be performed by adding the graft copolymer powder to the curable resin and mixing them. As described above, the graft copolymer according to the present invention has excellent powder dispersibility and can be directly dispersed in the powder phase of the curable resin. As a specific example, 2.4 of the curable resin composition prepared in the step (S30) may be mixed with the curable resin. The viscosity at 25°C at 1 / s may be 1,500 Pa.s or less, and specific examples include 1,450 Pa.s or less, 1,400 Pa.s or less, 1,350 Pa.s or less, 1,300 Pa.s or less, 1,290 Pa.s or less, 1,280 Pa.s or less, 1,270 Pa.s or less, 1,260 Pa.s or less, 1,250 Pa.s or less, 1,240 Pa.s or less, 1,230 Pa.s or less, or 1. , 220 Pa.s or less, and may be 100 Pa.s or more, 200 Pa.s or more, 300 Pa.s or more, 400 Pa.s or more, 500 Pa.s or more, 600 Pa.s or more, 700 Pa.s or more, 800 Pa.s or more, 900 Pa.s or more, 1,000 Pa.s or more, or 1,050 Pa.s or more, and within this range, the viscosity of the graft copolymer powder is low and the dispersibility is excellent.
[0083] The present invention also provides an adhesive composition comprising the curable resin composition. The adhesive composition may contain the curable resin composition as a toughening agent.
[0084] According to one embodiment of the present invention, the adhesive composition may include a base agent, a toughening agent, and a urethane resin, and the toughening agent may be the curable resin composition described above.
[0085] According to one embodiment of the present invention, the adhesive composition may contain the toughening agent in an amount of 10 wt % or more and 20 wt % or less, and specific examples thereof include 10 wt % or more, 11 wt % or more, 12 wt % or more, 13 wt % or more, or 14 wt % or more, and may contain 20 wt % or less, 19 wt % or less, 18 wt % or less, 17 wt % or less, or 16 wt % or less. By appropriately maintaining the content of the graft copolymer in the adhesive composition within this range, it is possible to simultaneously ensure impact resistance and adhesive strength.
[0086] According to one embodiment of the present invention, the base resin may be a thermosetting resin or a photocurable resin, and a specific example thereof may be one or more selected from the group consisting of an epoxy resin, a phenolic resin, an unsaturated polyester resin, a melamine resin, and a urea resin, and a more specific example thereof may be an epoxy resin. Taking into consideration the compatibility between the base resin and the toughening agent, the base resin may be the same curable resin as the curable resin of the toughening agent.
[0087] According to an embodiment of the present invention, the urethane resin may be any urethane resin that can be used in an adhesive composition without any particular limitation. In addition, the adhesive composition may further include a curing agent, a curing accelerator, a filler, a diluent, a moisture remover, etc. in addition to the base resin, the toughening agent, and the urethane resin.
[0088] According to an embodiment of the present invention, the curing agent may be at least one selected from the group consisting of an acid anhydride curing agent, an amine-based curing agent, and a phenol-based curing agent.
[0089] According to one embodiment of the present invention, the acid anhydride curing agent may be one or more selected from the group consisting of phthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, methylhimic anhydride, methylcyclohexene dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, ethylene glycol bistrimellitate, glycerol tristrimellitate, dodecenyl succinic anhydride, polyazelaic anhydride, and poly(ethyloctadecanedioic) anhydride.
[0090] According to an embodiment of the present invention, the amine-based curing agent is 2,5(2,6)-bis(aminomethyl)bicyclo[2,2,1]heptane, isophoronediamine, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, bis(4-amino-3-methyldicyclohexyl)methane, diaminodicyclohexylmethane, bis(aminomethyl)cyclohexane, metaphenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, diaminodiethyldiphenylmethane, diethyltoluenediamine, 3,3'-diaminodiphenylsulfone (3,3'-DDS), 4,4'-diaminodiphenylsulfone (4,4'-DDS), diaminodiphenylether (DADPE), bis(aminomethyl)cyclohexane, ... The diaminodiphenylamine may be one or more selected from the group consisting of aniline, benzyldimethylaniline, 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4,4'-diaminodiphenylmethane, 2,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 2,2'-diaminobiphenyl, 3,3'-diaminobiphenyl, 2,4-diaminophenol, 2,5-diaminophenol, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 2,3-tolylenediamine, 2,4-tolylenediamine, 2,5-tolylenediamine, 2,6-tolylenediamine, 3,4-tolylenediamine, methylthiotoluenediamine, diethyltoluenediamine, and dicyandiamide.
[0091] According to one embodiment of the present invention, the phenol-based curing agent may be at least one selected from the group consisting of phenol novolac resin, cresol novolac resin, bisphenol A, bisphenol F, bisphenol AD, and diallyl derivatives of bisphenols.
[0092] According to one embodiment of the present invention, the adhesive composition is applied to a cured specimen using an Advanced Rheometric Expansion System (ARS). In a graph showing a change in storage modulus (G') with temperature derived by dynamic viscoelastic analysis using a dynamic viscoelastic analysis system (ARES) (torsion mode, frequency 1 Hz, deformation rate (strain) 0.1%, and heating rate 5°C / min), the G' value shown at -35°C may be 900 MPa or more and 1,100 MPa or less, and specific examples thereof may be 910 MPa or more, 920 MPa or more, 930 MPa or more, 940 MPa or more, 950 MPa or more, 960 MPa or more, or 970 MPa or more, and may also be 1,100 MPa or less, 1,090 MPa or less, 1,080 MPa or less, 1,070 MPa or less, 1,060 MPa or less, 1,050 MPa or less, 1,040 MPa or less, 1,030 MPa or less, 1,020 MPa or less, 1,010 MPa or less, 1,000 MPa or less, or 990 MPa or less. Here, in the graph of change in storage modulus (G'), the G' value shown at -35°C is for predicting the change in fracture behavior due to the presence of the graft copolymer in the adhesive composition in the low temperature region. When the G' value shown at -35°C is within the above range, it has the effect of indicating that the adhesive composition has excellent impact resistance at low temperatures.
[0093] According to one embodiment of the present invention, the adhesive composition may have a storage modulus (G') value at 25°C in a graph of change in temperature as a function of temperature, which is derived from dynamic viscoelastic analysis (torsion mode, frequency of 1 Hz, strain of 0.1%, and heating rate of 5°C / min) using an Advanced Rheometric Expansion System (ARES) for a cured specimen. The G' value may be 530 MPa or more and 630 MPa or less, and specific examples of the G' value may be 535 MPa or more, 540 MPa or more, 545 MPa or more, 546 MPa or more, 547 MPa or more, 548 MPa or more, or 549 MPa or more, or may be 620 MPa or less, 610 MPa or less, 600 MPa or less, 590 MPa or less, 580 MPa or less, 570 MPa or less, or 560 MPa or less. Here, in the graph of change in storage modulus (G'), the G' value shown at 25°C is for predicting the change in fracture behavior due to the presence of a graft copolymer in the adhesive composition in the room temperature region. When the G' value shown at 25°C is within the above range, it has the effect of indicating that the adhesive composition has excellent impact resistance at room temperature.
[0094] According to one embodiment of the present invention, the adhesive composition may have a 25°C viscosity at 2.4 1 / s of 250 Pa.s or more and 750 Pa.s or less, and specific examples thereof include 250 Pa.s or more, 300 Pa.s or more, 350 Pa.s or more, or 400 Pa.s or more, and may be 750 Pa.s or less, 700 Pa.s or less, 650 Pa.s or less, 600 Pa.s or less, 550 Pa.s or less, or 500 Pa.s or less. When a curable resin composition is applied to the adhesive composition within this range, there is an effect of improving processability while providing excellent impact resistance.
[0095] According to an embodiment of the present invention, the adhesive composition may further include additives in addition to the base resin, toughening agent, and urethane resin. The additives may be release agents such as silicone oil, natural wax, and synthetic wax; powders such as crystalline silica, fused silica, calcium silicate, and alumina; fibers such as glass fiber and carbon fiber; flame retardants such as antimony trioxide; halogen trapping agents such as hydrotalcite and rare earth oxides; colorants such as carbon black and red iron oxide; and silane coupling agents.
[0096] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the exemplary embodiments set forth herein.
[0097] [Examples and Comparative Examples] [Example 1] <Production of Rubber Polymer Latex> In a polymerization reactor (autoclave) substituted with nitrogen, 75 parts by weight of ion-exchanged water, 60 parts by weight of 1,3-butadiene, 1.4 parts by weight of potassium rosinate, 0.6 parts by weight of potassium oleate, 0.9 parts by weight of potassium carbonate (K2CO3), 0.3 parts by weight of t-dodecyl mercaptan, and 0.3 parts by weight of potassium persulfate (K2S2O8) were added in one batch based on a total of 100 parts by weight of 1,3-butadiene, and polymerization was carried out at a reaction temperature of 70°C. Subsequently, when the polymerization conversion rate was 30% to 40%, 0.7 parts by weight of potassium oleate was added in one batch, and then 20 parts by weight of 1,3-butadiene was added in one batch, and polymerization was continued at a reaction temperature of 70°C. Then, after the polymerization conversion rate reached 60%, 20 parts by weight of 1,3-butadiene was added all at once, the reaction temperature was raised to 80°C, and the polymerization was continued until the polymerization conversion rate reached 95%. The total time required for the polymerization was 23 hours, the gel content of the obtained rubber polymer latex was 76%, and the average particle size of the rubber polymer particles was 300 nm.
[0098] In this case, the polymerization conversion rate was calculated as the ratio of the solid weight of the obtained rubber polymer to the solid weight of the input monomers.
[0099] <Production of graft copolymer latex> Based on a total of 100 parts by weight of rubber polymer latex (based on solid content), methyl methacrylate, n-butyl acrylate, and styrene, 75 parts by weight of the rubber polymer latex was added to a sealed polymerization reactor purged with nitrogen, and 200 parts by weight of ion-exchanged water, 0.2 parts by weight of potassium oleate, 0.036 parts by weight of ferrous sulfide, 0.2 parts by weight of sodium ethylenediaminetetraacetate, 0.2 parts by weight of sodium formaldehyde sulfoxylate, and 0.4 parts by weight of t-butyl hydroperoxide were added all at once. Then, 20 parts by weight of methyl methacrylate, 3.75 parts by weight of n-butyl acrylate, and 1.25 parts by weight of styrene were continuously added for 3 hours, and polymerization was carried out at a reaction temperature of 60°C for 4 hours to produce a graft copolymer latex. The final polymerization conversion rate was 99%, and the average particle size of the graft copolymer particles was 325 nm.
[0100] The polymerization conversion rate was calculated as the ratio of the solid weight of the obtained graft copolymer to the solid weight of the rubber polymer and monomers charged.
[0101] <Production of Graft Copolymer Powder> The prepared graft copolymer latex was diluted with distilled water to 15% by weight based on solid content, and then placed in a coagulation tank, and the internal temperature of the coagulation tank was increased to 45° C. Thereafter, IR1076 was added as an antioxidant based on 100 parts by weight based on the solid content of the graft copolymer, and the mixture was coagulated by stirring while adding an aqueous sulfuric acid solution, and the graft copolymer and water were separated, followed by dehydration and drying to prepare a graft copolymer powder.
[0102] [Example 2] The graft copolymer powder was produced in the same manner as in Example 1, except that the rubber polymer latex was added in an amount of 79 parts by weight instead of 75 parts by weight based on the solid content, methyl methacrylate was added in an amount of 16.8 parts by weight instead of 20 parts by weight, n-butyl acrylate was added in an amount of 3.15 parts by weight instead of 3.75 parts by weight, and styrene was added in an amount of 1.05 parts by weight instead of 1.25 parts by weight.
[0103] In this case, the final polymerization conversion rate of the produced graft copolymer latex was 98.5%, and the average particle size of the graft copolymer particles was 320 nm.
[0104] [Example 3] The graft copolymer powder was produced in the same manner as in Example 1, except that the rubber polymer latex was added in an amount of 80 parts by weight instead of 75 parts by weight based on the solid content, methyl methacrylate was added in an amount of 16 parts by weight instead of 20 parts by weight, n-butyl acrylate was added in an amount of 3 parts by weight instead of 3.75 parts by weight, and styrene was added in an amount of 1 part by weight instead of 1.25 parts by weight.
[0105] In this case, the final polymerization conversion rate of the produced graft copolymer latex was 98.3%, and the average particle size of the graft copolymer particles was 318 nm.
[0106] [Example 4] The graft copolymer powder was prepared in the same manner as in Example 1, except that the rubber polymer latex was added in an amount of 81 parts by weight instead of 75 parts by weight based on the solid content, methyl methacrylate was added in an amount of 15.2 parts by weight instead of 20 parts by weight, n-butyl acrylate was added in an amount of 2.85 parts by weight instead of 3.75 parts by weight, and styrene was added in an amount of 0.95 parts by weight instead of 1.25 parts by weight.
[0107] In this case, the final polymerization conversion rate of the produced graft copolymer latex was 98.4%, and the average particle size of the graft copolymer particles was 315 nm.
[0108] [Example 5] The graft copolymer powder was produced in the same manner as in Example 1, except that the rubber polymer latex was added in an amount of 83 parts by weight instead of 75 parts by weight based on the solid content, methyl methacrylate was added in an amount of 13.6 parts by weight instead of 20 parts by weight, n-butyl acrylate was added in an amount of 2.55 parts by weight instead of 3.75 parts by weight, and styrene was added in an amount of 0.85 parts by weight instead of 1.25 parts by weight.
[0109] In this case, the final polymerization conversion rate of the produced graft copolymer latex was 98.6%, and the average particle size of the graft copolymer particles was 310 nm.
[0110] [Example 6] The graft copolymer powder was prepared in the same manner as in Example 3, except that in the preparation of the rubber polymer latex, 1.5 parts by weight of potassium rosinate was added instead of 1.4 parts by weight, and 0.8 parts by weight of potassium oleate was added instead of 0.6 parts by weight.
[0111] In the preparation of the rubber polymer latex, the total time required for polymerization was 23 hours, the gel content of the obtained rubber polymer latex was 74%, and the average particle size of the rubber polymer particles was 250 nm.
[0112] The final polymerization conversion rate of the produced graft copolymer latex was 98.2%, and the average particle size of the graft copolymer particles was 270 nm.
[0113] [Example 7] The graft copolymer powder was prepared in the same manner as in Example 3, except that in the preparation of the rubber polymer latex, 1.3 parts by weight of potassium rosinate was added instead of 1.4 parts by weight, and 0.4 parts by weight of potassium oleate was added instead of 0.6 parts by weight.
[0114] In the preparation of the rubber polymer latex, the total time required for polymerization was 23 hours, the gel content of the obtained rubber polymer latex was 77%, and the average particle size of the rubber polymer particles was 350 nm.
[0115] The final polymerization conversion rate of the produced graft copolymer latex was 98.1%, and the average particle size of the graft copolymer particles was 370 nm.
[0116] [Example 8] The graft copolymer powder was prepared in the same manner as in Example 3, except that potassium oleate was added in an amount of 0.3 parts by weight instead of 0.2 parts by weight, and t-butyl hydroperoxide was added in an amount of 0.6 parts by weight instead of 0.4 parts by weight.
[0117] The final polymerization conversion rate of the produced graft copolymer latex was 98.7%, and the average particle size of the graft copolymer particles was 307 nm.
[0118] [Comparative Example 1] The graft copolymer powder was produced in the same manner as in Example 1, except that the rubber polymer latex was added in an amount of 73 parts by weight instead of 79 parts by weight based on the solid content, methyl methacrylate was added in an amount of 21.6 parts by weight instead of 16.8 parts by weight, n-butyl acrylate was added in an amount of 4.05 parts by weight instead of 3.15 parts by weight, and styrene was added in an amount of 1.35 parts by weight instead of 1.05 parts by weight.
[0119] In this case, the final polymerization conversion rate of the produced graft copolymer latex was 98.3%, and the average particle size of the graft copolymer particles was 340 nm.
[0120] [Comparative Example 2] The graft copolymer powder was prepared in the same manner as in Example 3, except that the rubber polymer latex was prepared by adding 1.7 parts by weight of potassium rosinate instead of 1.4 parts by weight, and 0.9 parts by weight of potassium oleate instead of 0.6 parts by weight, and the graft copolymer latex was prepared by adding 0.3 parts by weight of potassium oleate instead of 0.2 parts by weight, and 0.6 parts by weight of t-butyl hydroperoxide instead of 0.4 parts by weight.
[0121] In the preparation of the rubber polymer latex, the total time required for polymerization was 23 hours, the gel content of the obtained rubber polymer latex was 77%, and the average particle size of the rubber polymer particles was 220 nm.
[0122] The final polymerization conversion rate of the produced graft copolymer latex was 98.7%, and the average particle size of the graft copolymer particles was 230 nm.
[0123] [Comparative Example 3] The graft copolymer powder was prepared in the same manner as in Example 1, except that the rubber polymer latex was added in an amount of 85 parts by weight instead of 79 parts by weight based on the solid content, methyl methacrylate was added in an amount of 12 parts by weight instead of 16.8 parts by weight, n-butyl acrylate was added in an amount of 2.25 parts by weight instead of 3.15 parts by weight, and styrene was added in an amount of 0.75 parts by weight instead of 1.05 parts by weight.
[0124] In this case, the final polymerization conversion rate of the produced graft copolymer latex was 98.5%, and the average particle size of the graft copolymer particles was 305 nm.
[0125] [Experimental Example] [Experimental Example 1] For the rubber polymers and graft copolymers prepared in Examples 1 to 8 and Comparative Examples 1 to 3, the average particle diameters of the core and graft copolymers were measured and the shell thicknesses were calculated by the following methods, and the contents of each component and the method of adding the graft monomer during the preparation of the graft copolymers are shown in Tables 1 and 2 below.
[0126] In addition, the graft copolymer prepared in Example 3 was dried in a vacuum oven to obtain a solid, and then a thin section was made using a microtome. The thin section was stained with osmium tetroxide vapor to prepare a specimen. The specimen was photographed at 10,000 times magnification using a transmission electron microscope, and the shell thickness of each graft copolymer particle was measured and recorded, and the image is shown in FIG. 3.
[0127] *Average particle size (nm) of core and graft copolymer: The rubber polymer latex and graft copolymer latex prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were each diluted with distilled water to a concentration of 200 ppm, and then measured by dynamic light scattering (DLS) method according to ISO22412 using NICOMP380.
[0128] *Shell thickness (nm): The shell thickness was calculated from the average particle diameter of the core and the average particle diameter of the graft copolymer measured above according to the following mathematical formula 1.
[0129] [Mathematical formula 1] Shell thickness (nm) = average particle size of graft copolymer (nm) - average particle size of core (nm)
[0130] [Table 1]
[0131] [Table 2]
[0132] As shown in Table 1, it was confirmed that the graft copolymers prepared in Examples 1 to 8 had a core and a shell thickness controlled according to the range defined in the present invention.
[0133] In addition, as shown in FIG. 3, it was confirmed through a transmission electron microscope that the shell thickness of the graft copolymer prepared in Example 3 was controlled within the range defined by the present invention.
[0134] Meanwhile, as shown in Table 2, in Comparative Example 1, it was confirmed that the shell thickness increased as the core content decreased, in Comparative Example 2, it was confirmed that the average particle diameter of the graft copolymer decreased as the average particle diameter of the core decreased, and in Comparative Example 3, it was confirmed that the shell thickness decreased as the core content increased.
[0135] [Experimental Example 2] Using the graft copolymer powders prepared in Examples 1 to 8 and Comparative Examples 1 to 3, epoxy resin compositions in which the graft copolymers were dispersed in a curable resin composition were prepared by the following method.
[0136] <Preparation of Epoxy Resin Composition Having Graft Copolymer Dispersed> 63 parts by weight of epoxy resin (Kukdo Chemical, YD-128) and 37 parts by weight of the graft copolymer powder prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were added to a planetary mixer (KMTECH, KPLM-0.6) set at 70°C based on 100 parts by weight of the total content of epoxy resin and graft copolymer, and the mixture was stirred at 10 rpm for 1 hour, 80 rpm for 2 hours, and 60 rpm for 10 hours to disperse the graft copolymer powder in the epoxy resin, thereby preparing an epoxy resin composition in which the graft copolymer is dispersed.
[0137] The viscosity of the prepared epoxy resin composition was measured and is shown in Tables 3 and 4 below.
[0138] In addition, the epoxy resin composition prepared using the graft copolymer of Example 3 was cured at room temperature using polyetheramine, and a thin section was prepared using a microtome. The thin section was stained with osmium tetroxide vapor to prepare a specimen. The specimen was photographed at a magnification of 25,000 using a transmission electron microscope, and the core particle size and shell thickness of each dispersed phase were measured and the images are shown in FIG. 4.
[0139] At this time, the average core particle size calculated by taking the arithmetic mean of the measured core particle sizes was 294 nm, and the average shell thickness calculated by taking the arithmetic mean of the measured shell thicknesses was 19.5 nm.
[0140] * Viscosity at 25°C (Pa.s): The viscosity of the epoxy resin composition prepared above was measured at 25°C using a Rheometer (Antonpaar, MRC302), and the shear rate was 2.4s. -1 The viscosity values at 100 s are shown.
[0141] [Table 3]
[0142] [Table 4]
[0143] As shown in Tables 3 and 4, it can be seen that the epoxy resin compositions containing the graft copolymers of Examples 1 to 8 prepared within the range defined by the present invention have reduced viscosity compared to the epoxy resin compositions containing the graft copolymers of Comparative Examples 1 to 3. This confirms that the graft copolymers according to the present invention have excellent powder dispersibility in curable resins such as epoxy resins.
[0144] In addition, as shown in FIG. 4, it was confirmed through a transmission electron microscope that in the epoxy resin composition having the graft copolymer prepared in Example 3 dispersed therein, the core particle size of the graft copolymer as the dispersed phase was controlled according to the average core particle size range defined in the present invention, and the shell thickness was controlled according to the shell thickness range.
[0145] [Experimental Example 3] Using the epoxy resin composition prepared in Experimental Example 2, an adhesive composition was prepared in the following manner.
[0146] <Adhesive composition> The epoxy resin (Kookdo Chemical, YD-128) as the base material, the epoxy resin compositions (weight ratio of epoxy resin:graft copolymer powder=60:40) according to Examples 1 to 8 and Comparative Examples 1 to 3 prepared in Experimental Example 2 as toughening agents, urethane resin (Adeka, QR-9466), diluent (Kookdo Finechem, KFEPIOL-DE208), filler (fumed silica, Cabot, CAB-O-SIL TS-720), moisture remover (calcium oxide, Yuyoung Materials, UNI-OX), hardener (Evonik, Dicyanex 1400F), and hardener accelerator (Evonik, Amicure UR7 / 10) were mixed in the amounts shown in Table 3 below in a paste mixer. The mixture was mixed for 3 minutes at 600 rpm revolution and 500 rpm rotation using a mixer (KMTECH, PDM-300), and then degassed for 5 minutes at 600 rpm revolution and 200 rpm rotation to prepare an adhesive composition. The content of each component is based on 100 parts by weight of the total content of the base resin, toughening agent, urethane resin, and diluent.
[0147] The viscosity, impact peel strength, and dynamic viscoelasticity of the prepared structural adhesive compositions were measured by the following methods and are shown in Tables 5 and 6 below. Meanwhile, the impact peel strength and dynamic viscoelasticity were calculated by the following mathematical formula 2.
[0148] [Mathematical formula 2] Index = {(measured value in each Example and Comparative Example) / (measured value in Example 1)} x 100
[0149] *Impact peel strength (N / mm): The impact peel strength of the adhesive composition prepared above was measured according to ISO 11343. The size of the test piece was 90mmX20mmX1.6T (mm), and the size of one side to which the adhesive composition was applied was 30mmX20mm. After removing contaminants from one side of the test piece using ethanol, the prepared adhesive composition was applied. The thickness of the adhesive composition was kept constant using microbeads, and another test piece was covered and fixed on it, and then cured at 180°C for 30 minutes. After curing, the test piece was stabilized at 25°C and -35°C for more than 1 hour, and then a load was applied at a speed of 2m / sec using an impact strength tester (Instron, 9350) to measure the impact peel strength based on shear strength. In this case, the results measured in each example and comparative example were expressed as an index based on the result value measured in Example 1, and the higher the index, the better the impact resistance.
[0150] *Dynamic viscoelasticity (G', MPa): The adhesive composition prepared above was applied to a press mold in a thickness of 1 mm, and then pressed at 150°C for 30 minutes at a pressure of 20 MPa to cure. The prepared cured specimen was then cut into a size of 12.5 mm wide, 63.5 mm long, and 1 mm thick, and dynamic viscoelasticity analysis was performed using a rheometric system ARES (Advanced Rheometric Expansion System) G2 (TA Instruments) (temperature range -100°C to 200°C, heating rate 5°C / min, torsion mode, frequency 1Hz, deformation rate (strain) 0.1%). In the graph of the change in storage modulus (G') according to temperature derived from the dynamic viscoelasticity analysis, the G' values shown at 25°C and -35°C were confirmed. In this case, the results measured in each of the examples and comparative examples were expressed as an index based on the result value measured in Example 1, and the lower the index, the better the impact resistance due to the breaking strength.
[0151] [Table 5]
[0152] [Table 6]
[0153] As shown in Tables 5 and 6, the adhesive compositions prepared using the curable resin compositions prepared according to Examples 1 to 8 of the present invention as a toughening agent had low viscosity and excellent processability and workability, high impact peel strength and excellent impact resistance, and also had low storage modulus (G') due to dynamic viscoelasticity properties and excellent impact resistance due to fracture strength.
[0154] On the other hand, in the case of an adhesive composition prepared using as a toughening agent a curable resin composition including the graft copolymer of Comparative Example 1, in which the core content was low and the shell thickness was thick, the shell interacted with the urethane resin and the epoxy resin, causing swelling and reducing dispersibility, resulting in poor impact peel strength at both room temperature and low temperature, as well as poor impact resistance due to breaking strength at both room temperature and low temperature.
[0155] In addition, it was confirmed that the adhesive composition prepared by using as a toughening agent a curable resin composition containing the graft copolymer of Comparative Example 2, which had a small average core particle size, had a decrease in the average particle size of the graft copolymer in accordance with the decrease in the average particle size of the core, and had poor impact peel strength at both room temperature and low temperature due to an increase in viscosity when the graft copolymer was dispersed in the curable resin.
[0156] In addition, it was confirmed that the adhesive composition prepared by using as a toughening agent the curable resin composition including the graft copolymer of Comparative Example 3, which has a high core content and a thin shell thickness, can reduce swelling due to the interaction between the shell and the urethane resin and the epoxy resin, but the shell itself is reduced, resulting in reduced compatibility, and the impact resistance due to the breaking strength is poor both at room temperature and at low temperature.
[0157] From these results, it was confirmed that the graft copolymer of the present invention has excellent powder dispersibility in curable resins such as epoxy resins, can be dispersed in a curable resin composition by a powder phase dispersion method, and such a curable resin composition can be applied to the powder phase of the graft copolymer as an impact modifier, thereby having excellent productivity, and that the graft copolymer dispersed in the curable resin composition has excellent mechanical properties such as impact resistance, and that an adhesive composition containing the graft copolymer as a toughening agent has excellent impact resistance and adhesive strength.
Claims
1. A polymeric composition comprising a continuous phase and a dispersed phase, the continuous phase comprises a curable resin; the curable resin is an epoxy resin, the dispersed phase comprises a graft copolymer; The graft copolymer is a core-shell graft copolymer including a core containing a rubber polymer and a shell formed by graft polymerization of a graft monomer onto the rubber polymer, The rubber polymer contains conjugated diene monomer units, The graft copolymer comprises 75% by weight or more and 83% by weight or less of a core, The core has an average particle size of 250 nm or more and 400 nm or less, The thickness of the shell is 3 nm or more and 25 nm or less.
2. The curable resin composition according to claim 1 , wherein the graft monomer comprises an alkyl (meth)acrylate monomer.
3. The curable resin composition according to claim 1, wherein the graft monomer comprises a methyl (meth)acrylate monomer, an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms, and a crosslinkable monomer.
4. The curable resin composition according to claim 3 , wherein the crosslinkable monomer is polyethylene glycol diacrylate or allyl methacrylate.
5. The curable resin composition according to claim 1 , wherein the graft monomer further comprises an aromatic vinyl monomer.
6. The curable resin composition according to claim 1 , wherein the graft copolymer comprises from 79% to 81% by weight of a core and from 19% to 21% by weight of a shell.
7. The curable resin composition according to claim 1 , wherein the shell has a thickness of 5 nm or more and 22 nm or less.
8. The curable resin composition according to claim 1 , wherein the graft copolymer has an average particle size of 250 nm or more and 500 nm or less.
9. 2. The curable resin composition of claim 1, wherein the curable resin composition comprises from 50% to 99% by weight of a continuous phase and from 1% to 50% by weight of a dispersed phase.
10. 2. The curable resin composition according to claim 1, wherein the curable resin composition has a viscosity at 25° C. of 1,500 Pa.s or less at 2.4 1 / s.
11. An adhesive composition comprising a base agent, a toughening agent, and a urethane resin, The toughening agent is the curable resin composition according to claim 1, An adhesive composition comprising 10% by weight or more and 20% by weight or less of the toughening agent.
12. The adhesive composition according to claim 11, wherein a storage modulus (G') change graph according to temperature obtained by dynamic viscoelastic analysis (torsion mode, frequency 1 Hz, strain 0.1%, and heating rate 5°C / min) using an Advanced Rheometric Expansion System (ARES) on a cured specimen has a G' value of 900 MPa or more and 1,100 MPa or less at -35°C.
13. The adhesive composition according to claim 11, wherein the adhesive composition has a storage modulus (G') change graph according to temperature obtained by dynamic viscoelastic analysis (torsion mode, frequency 1 Hz, strain 0.1%, and heating rate 5°C / min) using an Advanced Rheometric Expansion System (ARES) on a cured specimen, the G' value shown at 25°C being 530 MPa or more and 630 MPa or less.
14. The adhesive composition according to claim 11, wherein the adhesive composition has a viscosity at 25°C at 2.4 1 / s of 250 Pa.s or more and 750 Pa.s or less.
Citation Information
Patent Citations
Production of polyolefin resin composition
JP1995324148A
Thermosetting resin composition and its use
JP2006104328A
Multilayer core-shell rubber polymer latex, method for producing the same, and acrylonitrile-butadiene-styrene graft copolymer containing the same
JP2015522693A
Polymer fine particle-containing curable resin composition having improved bonding strength against impact peeling
WO2016163491A1
Adhesive composition
WO2020022798A1